Efforts to Reduce Stunting Through the Bantul Seroja Programme: A Best Practice Perspective - Gumesa Rahma Jati; Eko Priyo Purnomo; Tiara Khairunnisa; Sirikanya Seti (Universitas Merdeka Malang, 2025)
The prevalence of stunting is still a serious health problem that requires special handling. Participate in accelerating the reduction of stunting in children under five, which is a priority program for the Government of Indonesia as stated in the National Medium-Term Development Plan (RPJMN) 2020–2024, the Bantul Regency Government with more than 45,000 children under five and stunting cases of around 3,056 children calculated per quarter of 2022 to develop a program called Bantul Sehat Ekonomi Karo Jamu (Bantul Seroja) to reduce stunting prevalence in Bantul Regency. This study aims to see how the implementation of the concept of Best Practice in public service innovations in Bantul Seroja through five stages of analysis, consisting of impact, partnership, sustainability, leadership, and transferability. Data collection uses secondary data techniques obtained indirectly through information available in the mass media, websites, articles, social media, and online news. This study shows that the public service innovations of Bantul Seroja get a good response from the community because they have an impact that can be felt directly under the urgency of the community's needs in the health sector.